Transregional Perspectives: Characterizing Obsidian Consumption at Early Chalcolithic Ein el-Jarba (N. Israel). (18th May 2020) - Carter, Tristan; Campeau, Kathryn; Streit, Katharina
ABSTRACT: This paper details the characterization of 48 obsidian artifacts from Ein el-Jarba, an Early Chalcolithic site of the southern Levantine Wadi Rabah culture (6th millennium cal b.c. ). By melding sourcing data from energy-dispersive X-ray fluorescence spectroscopy with the artifacts' techno-typological specifics, we contrast Ein el-Jarba's obsidian consumption practices with those of broadly contemporary and earlier communities in the context of the period's emergent transregional character. The results attest to a major reconfiguration of long-term traditions, with well-known Cappadocian and Lake Van region source materials now supplemented by obsidian from the Caucasus, such material's most southerly distribution. These diverse resources are believed to have circulated within the same exchange networks, mediated by communities of the Halaf culture to the north. Most of Ein el-Jarba's obsidian was in the form of pressure blades from a common technical tradition, the implements likely procured ready-made from the well-connected site of Hagoshrim.